COMPARATIVE REVIEW OF THE RISK ASSESSMENT QUANTITATIVE MODELS FOR PUBLIC OPEN SPACES LIGHTING DESIGN OPTIMISATION - Rakonjac, Ivan Milorad; Rakonjac, Ivana Milorad; Gasic, Milos Petar (Journal of Applied Engineering Science, 2017)
The key focus in the paper is on the presentation of the risk assessment model in the optimisation design process by establishing the link between the various phases that result in the successful project implementation. Through the comparative analysis of the quantitative risk assessment models a number of impacts on the design process are shown which occur in different project phases. This approach has proved the RAKA model (Risk Analysis by Key-factors Assessment) to be the most adequate mathematical model for the assessment of the risks on the project goals in the optimisation process of the development of the products for the accomplishing lighting of the open public spaces. The particularities of the model are best described by the predetermined criteria which contribute to the optimisation of the design process through the quantitative analysis of the project risks, according to the predetermined project goals sets. The influence of the risks on the project goals are shown by mathematical formulas in which the criteria of the design team are taken into account, leading to the efficiency improvement and enhancement in the implementation phases of the project.